Implementing Electronic Check-In/Check-Out to Reduce Challenging School Bus Behavior. Issue 3 (September 2021) - Hott, Brittany; Randolph, Kathleen M.; Josephson, Janet; Heiniger, Sarah
The purpose of this study was to explore the efficacy of an electronic check-in, check-out (eCICO) intervention. The district's case manager (i.e., guidance counselor) implemented the eCICO intervention remotely via FaceTime on an iPad in collaboration with the bus driver who facilitated student wireless internet access to a mobile hot spot. Results of the single-case multiple baseline across behaviors study suggest a functional relation between eCICO and the target bus behaviors of two rural students with emotional and behavioral disabilities. Further, low rates of target behaviors were maintained after eCICO was withdrawn. Implications for implementing eCICO interventions, limitations, and future research directions are discussed. Results of the study are reported using visual analysis, Tau-U, and percentage of non-overlapping data points.